Oxidative stress profiles in brain of fish (Diplodus sargus) upon exposure to mercury in organic and inorganic forms - Cardoso, Olívia Albuquerque (2015)
Fish brain demonstrated to be a target organ for organic mercury forms (mainly methylmercury – MeHg). However, there is little information on the neurotoxicity of divalent mercury (Hg(II)) and its ability to accumulate in fish brain. The prevalent information on MeHg is likely based in the perception of its higher toxicity associated with rapid uptake and distribution. Nevertheless, it has been also stated that the different forms of Hg share the same toxic chemical entity and, thus, neurotoxicity depends mainly on the environmental bioavailability. To clarify this research gap, two experiments comprising exposure and post-exposure periods were performed with juveniles of white seabream (Diplodus sargus), namely: experiment A - waterborne exposure to Hg(II) (2 ìg L-1); experiment B - dietary exposure to MeHg (8.7 ìg g-1). Both experiments followed the same experimental design, consisting in 4 exposure periods (E) (days 1, 3, 7 and 14) and 2 post-exposure periods (PE) (days 14 and 28). A control group was kept throughout both experiments in clean seawater or fed with uncontaminated food. At each time, brain was collected for determination of total Hg (tHg) (Experiment A), MeHg (experiment B) and oxidative stress endpoints (both experiments). Though Hg accumulation reached maximum values in brain of both experiments after 14 days of exposure, the highest levels were reached upon exposure to MeHg (7.0 ìg g-1 vs. 1.4 ìg g-1 for HgCl2). Interestingly, fish brain exposed to HgCl2 was not able to eliminate Hg, while MeHg levels decreased significantly in the post-exposure period (to a mean of 3.5 ìg g-1). Moreover, there was a poor activation of antioxidant defenses in fish brain exposed to Hg(II), mainly characterized by increase of superoxide dismutase (SOD) and glutathione reductase (GR) activities. The low protection afforded by antioxidants (confirmed by glutathione peroxidase (GPx) activity decrease) was probably on the basis of oxidative damage, as revealed by the enhancement of protein carbonyl groups in exposure and post-exposure periods. MeHg accumulation led to a different scenario, mainly characterized by an activation of antioxidant defenses (SOD, catalase (CAT), GPx, glutathione S-transferase (GST), total glutathione content (GSHt)) that were able to prevent oxidative damage on proteins and lipids. Despite the higher accumulation of MeHg in fish brain, there was a higher vulnerability of fish brain to Hg(II), depicted in the occurrence of oxidative damage and less responsiveness of the antioxidant systems. Thus, Hg(II) revealed a higher neurotoxicity potential, pointing out the relevance to consider this Hg form, together with MeHg, in further studies concerning wildlife and human health.